The Role of Organizational Commitment and Caring Behavior in Improving Nurses' Performance Through Extrinsic Rewards at Seto Hasbadi Hospital - Arham Irzan; Muhammad Fachruddin Arrozi Adhikara; Nofierni Nofierni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the effect of organizational commitment and caring behavior on nurse performance, with extrinsic reward as a mediating variable at Seto Hasbadi Hospital. The background of this study is based on the importance of nurse performance in supporting the effectiveness of hospital operations, as well as the effect of commitment and caring behavior on improving performance. The research method used is quantitative analysis with a cross-sectional research design. The number of samples was 140 nurses, selected using the Hair formula. The variables studied include organizational commitment, caring behavior, extrinsic reward, and nurse performance. Data collection was carried out through a questionnaire measured with a 4-point Likert scale. The analysis tool used is Structural Equation Modeling (SEM) with the SEM-AMOS application. The results showed that organizational commitment and caring behavior had a significant effect on nurse performance, both directly and indirectly through extrinsic reward. Extrinsic reward has a greater influence than organizational commitment and caring behavior, extrinsic reward is proven to mediate the relationship between the two independent variables with nurse performance. This study provides important implications for hospital management to focus on developing organizational commitment, nurse caring, extrinsic rewards to improve nurse performance.